2018
DOI: 10.1007/s11356-018-1330-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pesticides on the macroinvertebrate community in the water channels of the Río Negro and Neuquén Valley, North Patagonia (Argentina)

Abstract: Agriculture represents the second most important economic activity in the North Patagonian Region of Argentina and non-selective insecticides are still being used with significant implications to the quality of the environment. The range of concentrations (μg/L) determined for azinphosmethyl, chlorpyrifos, and carbaryl in drainage channels were from non-detected to 1.02, 1.45, and 11.21, respectively. Macroinvertebrate abundance and taxon richness in drainage channels were significantly lower in November compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 38 publications
1
14
1
1
Order By: Relevance
“…Assessing the impact of invasion on aquatic macroinvertebrate assemblages is important due to their crucial role in maintaining the structural and functional integrity of freshwater ecosystems (Wittmann et al, 2012;Zhang et al, 2014;Macchi et al, 2018). Macroinvertebrates regulate the geophysical condition of the sediments, participate in the decomposition of debris and the cycling of organic matter and nutrients, and regulate the primary producer communities (Pereira et al, 2012;Batzer and Boix, 2016;Zimmer et al, 2016;Boyero et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the impact of invasion on aquatic macroinvertebrate assemblages is important due to their crucial role in maintaining the structural and functional integrity of freshwater ecosystems (Wittmann et al, 2012;Zhang et al, 2014;Macchi et al, 2018). Macroinvertebrates regulate the geophysical condition of the sediments, participate in the decomposition of debris and the cycling of organic matter and nutrients, and regulate the primary producer communities (Pereira et al, 2012;Batzer and Boix, 2016;Zimmer et al, 2016;Boyero et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory effects on soil microbial functional diversity have been reported (Fang et al 2009). CP levels in Argentinian irrigation channels have been associated to a significant reduction of macroinvertebrate abundance and taxon richness (Macchi et al 2018). Freshwater crabs Barytelphusa guerini exposed to CP exhibited restlessness, escape behavior, increased scaphognathite activity, topsy-turving response and increased oxygen consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of this pesticide has been widely recorded. Concentrations up to 1.45 µg L − 1 have been measured in drainage channels of a 110-Ha section of an agricultural area near the Neuquén River (Argentina), with repeated exceedance of the LC 50 of monitored macroinvertebrates (Macchi et al 2018). The analysis of water samples collected from traditional wells, boreholes, and a lake in Burkina Faso between 2014 and 2016 showed that the threshold limit of 0.1 µg L − 1 has been exceeded two times in drinking water sources, while CP detection in water was systematically associated with a risk for the environment (Lehmann et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gaillard et al (2016a) estimated PPP concentrations of up to 20 µg.L -1 in streams located in headwater agricultural catchments. Moreover, PPPs can affect the health of wild organisms such as macroinvertebrates (MIs) (Macchi et al 2018), amphibians (Slaby et al 2019), fish (Clasen et al 2018), and birds (Stanton et al 2018;Brain and Anderson 2019), and biodiversity in general (McLaughlin and Mineau 1995;Geiger et al 2010). Bioaccumulation and bioamplification along the trophic chain are of particular concern as they may result in increased contamination levels in top predators (Konwick et al 2006;Rostron 2010).…”
Section: Introductionmentioning
confidence: 99%